Urgent Investigation in the Light of Historical- Legal Analysis - Petrović, Borislav (Kriminalističke teme, 2002)
One of the aim of historical-legal analysis is reflected tn confirmation of accuracy and consistency of our positive legal solutions in the field of urgent (anticipated) inspection of properties and persons, temporary repossession of objects, conduct of investigation and expertise. In that way we will be able to see advantages but also disadvantages of our legal solutions, especially because law of criminal conduct in BiH was brought only few years ago. Apart from that this comparative analysis is relevant because of criminal legal reform in our country, since in this area we are expected to have significant changes and additions. This points out that some positive legal solutions in court practice have not been the most effective. So, by applying historical legal method we will highlight some conditions and causes in development of certain positive legal solutions that refer to these four urgent investigative acts.